Highly exposed and activity modulated sandwich type Pt thin layer catalyst with enhanced utilization - Balan, Beena K.; Kurungot, Sreekumar (Journal of Materials Chemistry, 2011)
A Pt thin layer catalyst supported on an in situ prepared `RuO(2)-carbon-RuO(2)' sandwich type hybrid support is presented. This is achieved by the extensive functionalization of a hollow carbon nanofiber support to introduce oxygen containing functional groups (FCNF) with the specific aim to accomplish the exclusive adsorption of Ru ions along its inner cavity and outer surfaces. Preferential adsorption of Ru ions from a mixture of Pt and Ru with sufficient time for adsorption and reorganization of ions on the carbon nanofiber surface leads to the in situ renovation of FCNFs to form a hybrid `RuO(2)-carbon-RuO(2)' sandwich type support followed by Pt nanoparticle decoration. While the selective exposure of Pt on the hybrid support surface is confirmed from the HRTEM analysis, the electronic changes effected in the CNF support are evident from the XPS and XRD analysis. Finally, the potential benefit of such a design is also demonstrated using electrochemical studies, where the three-fold increase in the electrochemically active surface area from cyclic voltammetric analysis, a four-fold improvement in the limiting current density coupled with a 80 mV gain in onset potential from rotating disc electrode studies for the oxygen reduction reaction, and a drastic reduction in the CO poisoning for methanol oxidation reaction underlines the superb performance of this material. Such an exceptionally high performance can be attributed to the strong electronic perturbations occurring in the Pt and the FCNF support due to the presence of a continuous RuO(2) layer in between. Such a high aspect ratio core-shell type design with an unusual enhancement in the Pt utilization establishes the roles of both the hybrid support and active catalyst to address the future challenges in the area of utilization improvement.